Cover Crops and Fertilization Alter Nitrogen Loss in Organic and Conventional Conservation Agriculture Systems - Shelton, Rebecca E.; Jacobsen, Krista L.; McCulley, Rebecca L. (Frontiers in Plant Science, 2018)
Agroecosystem nitrogen (N) loss produces greenhouse gases, induces eutrophication, and is costly for farmers; therefore, conservation agricultural management practices aimed at reducing N loss are increasingly adopted. However, the ecosystem consequences of these practices have not been well-studied. We quantified N loss via leaching, NH3 volatilization, N2O emissions, and N retention in plant and soil pools of corn conservation agroecosystems in Kentucky, USA. Three systems were evaluated: 1) an unfertilized, organic system with cover crops hairy vetch (Vicia villosa), winter wheat (Triticum aestivum), or a mix of the two (bi-culture); 2) an organic system with a hairy vetch cover crop employing three fertilization schemes (0 N, organic N, or a cover crop N-credit approach); and 3) a conventional system with a winter wheat cover crop and three fertilization schemes (0 N, urea N, or organic N). In the unfertilized organic system, cover crop species affected NO3-N leaching (vetch > bi-culture > wheat) and N2O-N emissions and yield during corn growth (vetch, bi-culture > wheat). Fertilization increased soil inorganic N, gaseous N loss, N leaching, and yield in the organic vetch and conventional wheat systems. Fertilizer scheme affected the magnitude of growing season N2O-N loss in the organic vetch system (organic N > N-credit) and the timing of loss (organic N delayed N2O-N loss vs. urea) and NO3-N leaching (urea >> organic N) in the conventional wheat system, but had no effect on yield. Cover crop selection and N fertilization techniques can reduce N leaching and greenhouse gas emissions without sacrificing yield, thereby enhancing N conservation in both organic and conventional conservation agriculture systems.